New Clinton administration and the Caribbean : trade, security and regional politics. - BRYAN, Anthony T. (1997)
Discusses the policy challenges faced by the US in the Caribbean, viz: (i) how, and in what manner, the US should ensure that Caribbean countries are not completely disadvantaged by the new trading arrangements and (2) what are matters of a political and security nature in which the US should seek cooperation with the Caribbean. Suggests that there is scope for the United States to construct a policy of mutual benefit to itself and to the Caribbean.